PENGARUH PRAKTIK KERJA LAPANGAN DAN SOFT SKILL TERHADAP KESIAPAN KERJA SISWA KELAS XII PROGRAM KEAHLIAN MANAJEMEN PERKANTORAN DI SMK NEGERI 10 SURABAYA - Nabila Rayes, Abrarul; Puspasari, Durinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocational high school (SMK) graduates are expected to enter the workforce with adequate readiness, yet national labor data still place SMK graduates as the largest contributor to open unemployment. This study examines the effect of field work practice (PKL) and soft skills on the work readiness of twelfth-grade students majoring in Office Management at SMK Negeri 10 Surabaya. A quantitative explanatory approach was used, with data collected through a Likert-scale questionnaire distributed to 101 students selected through purposive sampling out of a population of 136. Data were analyzed using multiple linear regression with the help of SPSS. The results show that PKL has a positive and significant partial effect on work readiness, soft skills also have a positive and significant partial effect, and both variables simultaneously affect work readiness with a contribution of 54.5%, while the remaining 45.5% is explained by other factors outside this study. These findings support Human Capital Theory, which views work experience and skill development as forms of human capital investment, and suggest that schools need to strengthen partnerships with industry and integrate soft skill development into learning activities so that graduates are better prepared to face the demands of the labor market.